The role of pro-fibrotic biomarkers in paroxysmal and persistent atrial fibrillation - Stanciu, Adina Elena; Vatasescu, Radu Gabriel; Stanciu, Marcel Marian; Serdarevic, Nafija; Dorobantu, Maria (Cytokine (Philadelphia, Pa.), 2018)
•AF progression is associated with a gradual increase in NT-proBNP, IL-6, MMP-9/TIMP-1.•TGF-β1 was lower in persistent AF than in paroxysmal AF and non-AF controls.•TGF-β1 was negatively correlated with NT-proBNP and LA diameter in AF.•AF progresses despite compensatory changes in the TGF-β1 signaling pathway. Signaling pathways involved in electrical, structural and contractile remodeling processes behind development and progression of atrial fibrillation (AF) have not been completely elucidated, but it seems to be related to complex interactions among neurohormonal and cellular mediators. We aimed to investigate interleukin-6 (IL-6), transforming growth factor-beta1 (TGF-β1), matrix metalloproteinase-9 (MMP-9), tissue inhibitor of metalloproteinase-1 (TIMP-1), as biomarkers of atrial remodeling, in patients with paroxysmal and persistent AF, and their correlation with N-terminal prohormone of brain natriuretic peptide (NT-proBNP) and left atrial (LA) diameter. Thirty-seven patients (22M/15F) with paroxysmal AF, 32 patients (22M/10F) with persistent AF and 30 healthy control subjects (18M/12F) were enrolled in the study. Serum levels of biomarkers were measured by ELISA. Cardiac function was assessed echocardiographically. IL-6 levels and MMP-9/TIMP-1 ratio were significantly higher in AF patients than in non-AF controls (P < .001), and in persistent than in paroxysmal AF (P < .001), in line with NT-proBNP and LA diameter. In contrast, TGF-β1levels declined with increasing AF duration (from 51.2 pg/mL, IQR: 38.9–87.9 pg/mL in paroxysmal to 23.9 pg/mL, IQR: 16.9–43.6 pg/mL in persistent AF). TGF-β1 was negatively correlated with NT-proBNP (r = −0.53, P = .001 in paroxysmal AF and r = −0.71, P < .001 in persistent AF) and LA diameter (r = −0.44, P = .006 in paroxysmal AF and r = −0.51, P = .003 in persistent AF). Our results demonstrate that AF development and progression (from paroxysmal to persistent) is associated with a gradual increase in serum levels of NT-proBNP, IL-6 and MMP-9/TIMP-1 ratio. Moreover, this study suggests that the relationship between TGF-β1, NT-proBNP and LA diameter allows for the progression of atrial remodeling during AF, despite compensatory changes in the TGF-β1 signaling pathway.